Chiral Non‐Fullerene Acceptor Enriched Bulk Heterojunctions Enable High‐Performance Near‐Infrared Circularly Polarized Light Detection. Issue 31 (9th July 2022) - Liu, Lixuan; Yang, Yang; Zhu, Lingyun; Zhang, Jianqi; Chen, Kun; Wei, Zhixiang
Abstract: Organic photodetectors that can sensitively convert near‐infrared (NIR) circularly polarized light (CPL) into modulable electrical signals have promising applications in spectroscopy, imaging, and communications. However, the preparation of chiral NIR organic photodetectors with simultaneously high dissymmetry factor, responsivity, detectivity, and response speed is challenging. Here, direct CPL detectors based on the bulk heterojunctions (BHJs) of chiral BTP‐4Cl non‐fullerene acceptor with dilute achiral PM6 donor are constructed, which successfully address these issues. The chiral acceptor‐enriched BHJs with a donor/acceptor ratio of 1/10 achieve an optimal trade‐off between chiroptical properties and optoelectronic performance. The supramolecular chirality from the acceptor aggregates provides the BHJs with a true absorption dissymmetry factor ( g abs ) of ±0.02 at 830 nm, the highest value among NIR‐sensitive detectors, which endows the photodetector with a photocurrent dissymmetry factor ( g sc ) of ±0.03. Impressively, the photodetector demonstrates an external quantum efficiency as high as 60%, a responsivity of 0.4 A W −1, a detectivity of 3 × 10 11 Jones (based on noise current), and a fast response speed on the microsecond scale with the −3 dB bandwidth over 7000 Hz in the NIR region. This study exhibits a promising strategy for building high‐performing direct NIR CPL detectors by introducing supramolecular chirality into BHJs. Abstract : Chiral non‐fullerene acceptor‐enriched bulk heterojunctions are developed for a broadband circularly polarized light (CPL)‐sensitive detection ranging from 300 to 950 nm. The device demonstrates a distinguished CPL detection capability with a dissymmetry photocurrent factor of ±0.03 at 830 nm, providing superior properties for organic NIR‐sensitive CPL detectors.